THE INFANT MASSAGE AS AN INTERVENTION TOOL IN THE DEVELOPMENT OF DOWN SYNDROME BABIES. PILOT STUDY - Piñero-Pinto , E; Jiménez-Rejano , J J; Rebollo-Roldán , J (Cuestiones de Fisioterapia, 2018)
Objective: to know the effects of infant massage on the maturational development of the baby with Down syndrome in the short term, attending to all areas of development. Material and method: two groups of 11 babies are compared, experimental group, which receives infant massage, and control group, which does not receive treatment. The developmental variables (developmental quotient, partial and global developmental ages) are measured twice, 5 weeks apart with the Early Childhood Psychomotor Development Scale Brunet–Lézine–Revised.Results: both groups improve with time, but the experimental group does it in all variables, both in relation to the age of development and to the development quotients, which aspect is not observed in the control group. In the variables related to the maturational age there were significant differences between the groups, the results being better in all the cases in the experimental group. In the age of global development, the mean of the pre-treatment post-treatment differences was significantly higher in the experimental group [47.45 (SD = 12.36)] compared to the control group [26.64 (SD = 16.35)]. In the global development quotient, the mean difference of the change between the pre-post-treatment scores between the groups was 10.21 points [CI 3.41; 17.02]. The 2x2 mixed model of variance analysis indicated a statistically significant group-by-time interaction for all development ratios, with those of the experimental group being better. Conclusion: infant massage is a procedure that seems to improve the maturational development of babies with Down syndrome in the short term of the applied sample.